Three Type Layout Pattern Setup Intercrops and Their Influence on Early Growth of Castor Plant (Jatropha curcas) in the Tumpangsari System - Abdillah Ikhrom (Contributions of Central Research Institute for Agriculture, 2022)
The research showed that the observations made on jatropha from 60 to 180 HST in general had a significant effect on all observed parameters but differed at the age of observation. Parameters of plant length were significantly different from 150 dap of observation, plant height, shoot stem length, number of leaves and canopy width from 120 dap, shoot length from 90 dap, leaf area and leaf area index from 60 dap and the number of shoots was only different significant at the age of observation 60 dap while at 90 to 150 dap was not significantly different. The results of this study also show that planting eggplant on Jatropha land in two cropping patterns will significantly affect Jatropha growth. while for tomato and chili intercrops planted on jatropha plantations using two planting models, it shows that jatropha growth is still relatively good. Based on the estimated calculation of the economic value of the intercrops, it can be seen that the highest economic value is obtained from the planting of the intercrops of the eggplant, both the treatment of the planting pattern with the same spacing in all directions and square spacing with R/C Ratio values of 2.74 and 2.2, then intercrops of chili with R/C Ratio values were 2.12 and 2.11 and the lowest values were shown by the results of tomato intercrops with R/CRatio values of 2.04 and 1.99.